Experimental Infection of Common Eider Ducklings with Wellfleet Bay Virus, a Newly Characterized Orthomyxovirus - Shearn-Bochsler, Valerie; Ip, Hon Sang; Ballmann, Anne; Hall, Jeffrey S.; Allison, Andrew B.; Ballard, Jennifer; Ellis, Julie C.; Cook, Robert; Gibbs, Samantha E.J.; Dwyer, Chris
Wellfleet Bay virus (WFBV), a novel orthomyxovirus in the genus Quaranjavirus, was first isolated in 2006 from carcasses of common eider (Somateria mollissima) during a mortality event in Wellfleet Bay (Barnstable County, Massachusetts, USA) and has since been repeatedly isolated during recurrent mortality events in this location. Hepatic, pancreatic, splenic, and intestinal necrosis was observed in dead eiders. We inoculated 6-week-old common eider ducklings with WFBV in an attempt to recreate the naturally occurring disease. Approximately 25% of inoculated eiders had onset of clinical disease and required euthanasia; an additional 18.75% were adversely affected based on net weight loss during the trial. Control ducklings did not become infected and did not have clinical disease. Infected ducklings with clinical disease had pathologic lesions consistent with those observed during natural mortality events. WFBV was reisolated from 37.5% of the inoculated ducklings. Ducklings surviving to 5 days postinoculation developed serum antibody titers to WFBV.